Pengaruh Citra Merek, Elecronic Word of Mouth dan Kualitas Pelayanan Terhadap Keputusan Pembelian: Studi Kasus Konsomen Shopee di Kecamatan Malausma - Tanti Amalia; Halimah Zahrah (Indo Publishing, 2026)
The rapid growth of e-commerce has significantly transformed consumer behavior in purchase decision-making, particularly through the roles of brand image, electronic word of mouth, and service quality. Increasing market competition requires digital platforms to build consumer trust and deliver positive experiences in order to maintain business sustainability. This study aims to analyze the influence of brand image, electronic word of mouth, and service quality on the purchase decisions of Shopee consumers in Malausma District. The research employs a quantitative approach with a causal associative design. Data were collected through a survey of consumers who had previously made purchases on Shopee and were analyzed using multiple linear regression techniques. The findings indicate that brand image, electronic word of mouth, and service quality exert a positive influence on purchase decisions, both partially and simultaneously. A strong brand image is able to shape consumer perceptions and confidence, while electronic word of mouth serves as an important information source that affects consumer attitudes and purchase intentions. Meanwhile, high service quality enhances consumer trust and comfort in conducting transactions. These findings highlight the importance of integrated digital marketing strategies through brand strengthening, effective management of consumer reviews, and continuous improvement of service quality to encourage purchase decisions on e-commerce platforms.